Told again : old tales told again - De la Mare, Walter, 1873-1956 (Oddly modern fairy tales., 2015)
Nineteen classic fairy tales, retold for younger readers in the early twentieth-century, including "Rapunzel," "Little Red Riding-Hood," "Rumpelstiltskin," and "The Sleeping Beauty."